фото анық болмай қалды. Телефоным камерасы дұрс емес түсінбеген жеріңде сұра комментке айтам ок
2х(2х + 4) - ( 2х - 3)(2х + 3) = -7.
4x^2 + 8x - ( 4x^2 + 6x - 6x - 9) +7 = 0
4x^2 + 8x - 4x^2 - 6x +6x +9 +7 = 0
8x - 6x +6x +9 +7 = 0
8x +9 +7 = 0
8x + 16 = 0
8x = -16
x = -2
ответ: -2,0
Объяснение:
фото анық болмай қалды. Телефоным камерасы дұрс емес түсінбеген жеріңде сұра комментке айтам ок
2х(2х + 4) - ( 2х - 3)(2х + 3) = -7.
4x^2 + 8x - ( 4x^2 + 6x - 6x - 9) +7 = 0
4x^2 + 8x - 4x^2 - 6x +6x +9 +7 = 0
8x - 6x +6x +9 +7 = 0
8x +9 +7 = 0
8x + 16 = 0
8x = -16
x = -2
ответ: -2,0
Объяснение: